Study of fluid flow in pre drilled liners in producing horizontal wells (Research, Society and Development, 2019)
Horizontal oil wells, when compared to vertical wells, have the main advantage of a larger area open to flow. The oil flowing from the porous medium enters the interior of the horizontal duct by means of several holes of small diameter, made in the metallic wall of the duct. The radial flow in the bore becomes axial along the duct, causing increased pressure drop. Therefore, this undesirable effect must be minimized, such that the flow is not impaired. That is the purpose of this work. The influence of the radial inflow on the pressure profile and axial flow velocity was investigated when the viscosity values of the fluid and the number of holes per plane were varied. The flow under analysis is characterized by a monophasic, incompressible, turbulent and permanent regime, occurring in a horizontal pipe 3 meters long and 10 cm in diameter. The 1 cm diameter holes in the tubing allow the ingress of fluid radially. Numerical modeling was performed using the ANSYS FLUENT 15.0 software, with post-processing and data collection through CFD-Post. Preliminary results show that the presence of radial fluid inlet generates an increase in pressure differential along the pipe due to the restriction to axial flow. Such a restriction is generated by the appearance of a hydrodynamic barrier from radial inflow. It has also been observed that more viscous fluids require higher pressure gradients to flow, however, they suffer smaller pressure drops when exposed to radial inflows. As for the velocity profiles, increasing the viscosity of the flowing fluid resulted in the intensification of the axial velocity after the radial inflow to a certain extent, so that for very viscous fluids this behavior is not conserved. Finally, the increase in axial flow velocity also occurs, the greater the number of holes per plane in the tube.